Pengaruh Motivasi, Beban Kerja dan lingkungan Kerja Terhadap Produktivitas Kerja Karyawan PT. Kanaan Sukoharjo - Susanti Faridah; Pamilia Sulistyowati (Yayasan Literasi Sains Indonesia, 2022)
The t-test related to the motivation to work productivity of employees of PT. Kanaan Sukoharjo obtained the results of t count = 14,589> t table = 1,960 then there is an effect. The t-test related to the workload of the employee's work productivity at PT. Kanaan Sukoharjo. The results obtained t count = 22,025> t table = 1,960 then there is an influence between Workload on Work Productivity of Employees of PT. Kanaan Sukoharjo. The t-test related to the work environment on employee productivity at PT. Kanaan Sukoharjo. The result of t count = 5,624> t table = 1,960 then there is an influence between the Work Environment on Work Productivity of Employees of PT. Kanaan Sukoharjo. Together, Motivation, Workload, Work Environment on Employee Work Productivity of PT. Kanaan Sukoharjo obtained the results of F arithmetic = 406.516> F table = 2.6, then there is a joint influence. R2 is 0.816 or 81.6%, meaning that together there is an influence between the independent variables, namely Motivation, Workload, Work Environment on Work Productivity of Employees of PT. Kanaan Sukoharjo amounted to 81.6%, while the 18.4% was influenced by other factors, which were not examined such as leadership, work placement, organizational culture and others.